The influence of E-Commerce live streaming on customer purchase intention among student in UMK Pengkalan Chepa - Muhamad Zaidani Zakaria; Nuha Mohamad Fadzil; Nurul Natasya Aziz; Sharmila Palany Samy (2024)
E-commerce live streaming has become a popular and effective way for businesses to reach and engage with consumers (Jiang, 2022). It allows companies to showcase their products and services in real-time, providing a more immersive and interactive shopping experience for customers. This method allowing businesses to connect with their audience on a more personal level, answer questions in real-time, and build trust and credibility (Febriany et al., 2023). E-commerce live streaming also allows consumers to make informed purchasing decisions by providing them with valuable information and demonstrations of products (Li et al., 2022). Furthermore, e-commerce live streaming often includes online activities and promotions to entertain and engage customers, creating a sense of excitement and urgency to encourage purchases.